Active Peptide AR-9 From Eupolyphaga sinensis Reduces Blood Lipid and Hepatic Lipid Accumulation by Restoring Gut Flora and Its Metabolites in a High Fat Diet–Induced Hyperlipidemia Rat - Wang, Hong; Dong, Pingping; Liu, Xin; Zhang, Zhen; Li, Huajian; Li, Yanan; Zhang, Jiayu; Dai, Long; Wang, Shaoping (Frontiers in Pharmacology, 2022)
The dysbiosis of gut flora and its metabolites plays important roles in the progression of hyperlipidemia (HL), and some bioactive peptides are available for HL treatment. In this study, we aimed to isolate an active peptide (AR-9) from active peptides of E. sinensis (APE) and determine whether AR-9 could improve many symptoms of a HL rat induced by a high-fat diet (HFD) by modulating gut flora and its metabolites. Above all, AR-9 was derived from APE using ion-exchange chromatography, and its structure was deconstructed by Fourier transform infrared spectrometer (FT-IR), circular dichroism (CD) spectroscopy, and UHPLC-Q-Exactive-Orbitrap MS. Then, an HFD-induced HL model in SD rats was established and used to clarify the regulatory effects of AR-9 (dose of 3 mg/kg) on HL. Normal diet–fed rats were taken as the control. The plasma samples and liver were harvested for biochemical and histopathological examinations. 16S rRNA gene sequencing and untargeted metabolomics were sequenced to assess changes in gut flora and its metabolites from rat fecal samples. Finally, Spearman’s correlation analysis was used to assess the relationship between lipid-related factors, gut flora, and its metabolites so as to evaluate the mechanism of AR-9 against HL. The results of the separation experiments showed that the amino acid sequence of AR-9 was AVFPSIVGR, which was a fragment of the actin protein from Blattaria insects. Moreover, HFD rats developed exaltation of index factors, liver lipid accumulation, and simple fibrosis for 8 weeks, and the profiles of gut flora and its metabolites were significantly altered. After treatment, AR-9 decreased the levels of lipid factors in plasma and the extent of liver damage. 16S rRNA gene sequencing results indicated that AR-9 significantly increased the relative abundance of beneficial bacteria Bacteroidetes and reduced the relative abundance of the obesity-associated bacteria Firmicutes. Furthermore, AR-9 changed gut microbiota composition and increased the relative abundance of beneficial bacteria: Lactobacillus, Clostridium, Dehalobacterium, and Candidatus arthromitus. Fecal metabolomics showed that the pathway regulated by AR-9 was “arginine biosynthesis”, in which the contents were citrulline and ornithine. Spearman’s correlation analysis revealed that two metabolites (ornithine and citrulline) showed significantly negative correlations with obesity-related parameters and positive correlations with the gut genera (Clostridium) enriched by AR-9. Overall, our results suggested interactions between gut microbial shifts and fecal amino acid/lipid metabolism and revealed the mechanisms underlying the anti-HL effect of AR-9. The abovementioned results not only reveal the initial anti-HL mechanism of AR-9 but also provide a theoretical basis for the continued development of AR-9.